Reform Of The Criminal Procedure Law And Criminal Law Enforcement In Indonesia - Arjoni Putra; Sungeng Dwiono; M. Galib Iqbal (LEGAL BRIEF, 2024)
Criminal Procedure Law (HAP) reform and criminal law enforcement in Indonesia are the main focus in the dynamic development of the criminal justice system. This abstract explores the significant changes in the Criminal Procedure Law implemented since the last few years and their impact on criminal law enforcement in Indonesia. The updates include revisions to provisions in the Code of Criminal Procedure, the introduction of technology in the judicial process, and measures to improve the efficiency and transparency of the criminal justice system. The study also analyzed the response of authorities and communities to the reforms, and evaluated their impact on justice, human rights, and the effectiveness of criminal law enforcement in Indonesia. The results of the study provide an in-depth understanding of changes in criminal procedural law and the dynamics of law enforcement in Indonesia, creating a foundation for continued debate and evaluation of future legal policies.